Programas físico-esportivos para pessoas com deficiência: propostas e experiências no Estado de São Paulo - Andrade, Andresa Caravage de (2019)
The purpose of this study is to discuss about the possibilities of participation for people with disabilities in physical-sports programs developed in the state of São Paulo. For this intent, were selected the cities chosen by the Brazilian Federal Government in 2013 to receive the Sports Initiation Centers (CIEs). Initially, was carried out a documentary research in the proposed letters of the 56 cities with the CIE in state of São Paulo, consultation and analysis in legislative documents and public data provided by the Brazilian Institute of Geography and Statistics (IBGE) in the survey of sport profile of the Brazilian states and municipalities, in order to understand the organization of sports management in Brazil. In addition, the para-athlete’s profiles who participated in the School Paralympics Games and the São Paulo Regional Games in 2016, 2017 and 2018 were also analyzed. It was observed that actions, projects and programs for people with disabilities are present in all sporting dimensions, that sports and rights councils for people with disabilities are infrequent and very few active – and they are unable to influence the sport policies of the sector, and the fact that there is predominant participation of physically disabled men in Paralympics sporting competitions. In the field research were interviewed the managers of the State Secretariat of the Rights of Persons with Disabilities, the Sport State Secretariat and the Brazilian Paralympic Committee. The municipalities of Barueri, Campinas and Jundiaí were chosen for local managers interviews and for a brief observation of the identified programs. The selected cities have different management ways in the sport area: through the resources transfer to associations, partnership with the Municipal Secretariat of the Rights of Persons with Disabilities or by the Sport Municipal Secretariat itself. The managers highlighted the post-event resource's reduction for sports, the public system bureaucracy, the lack of adequate sports structures, the Brazilian clubs-centered sports model, sport as way to social insertion, the value of articulation and partnerships mainly with universities, as well the professional qualification and the experiences exchange between neighboring municipalities. Given the limitations and possibilities of sports management, from the managers and local experiences, it's hoped that data can be extrapolated to understand similar realities.